Study on the performance of leaky bucket policing for heterogeneous traffic - Rajenikanth Anbanandan (2008)
Several factors determine the mechanisms deployable for congestion control in ATM networks. The Leaky Bucket is recognized as one of the best forms of traffic regulators for controlling the rate at which the source generates traffic. When a source enters into a traffic contract with the network, it specifies different traffic characteristics like peak cell rate, sustainable cell rate, minimum cell rate and maximum burst size. As long as the source submits traffic within the limits specified in the contract, the policing mechanism remains inactive. When the contract is abused, the policing mechanism comes into effect. The violating cells are dropped or tagged and thus, preventing the network from getting congested further downstream. In this research, the effect of Leaky Bucket policing on Real-Time Variable Bit Rate traffic and Non-Real-Time Variable Bit Rate traffic is explored. The Cell Loss Ratio, ATM Virtual Circuit Load and TCP Traffic delay are also investigated.*